Beef up your competitor: a model of advertising cooperation between internet search engines - Geza Sapi; Irina Suleymanova (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We propose a duopoly model of competition between internet search engines endowed with different technologies and study the effects of an agreement where the more advanced firm shares its technology with the inferior one. We show that the superior firm enters the agreement only if it results in a large enough increase in demand for advertising space at the competing .rm and a relatively small improvement of the competitor's search quality. Although the superior firm gains market share, the agreement is beneficial for the inferior firm, as the later firm's additional revenues from a higher advertising demand outweigh its losses due to a smaller user pool. The cooperation is likely to be in line with the advertisers' interests and to be detrimental to users' welfare.
Keywords: L13; L24; L86; M37; 330; Search engine; two-sided market; advertising; strategic complements; technology; Suchmaschine; Internet; Online-Werbung; Technologie; Lizenzvergabe; Unternehmenskooperation; Oligopol; Wohlfahrtseffekt; Theorie